Identificación de insectos polinizadores, usando la aplicación iNaturalist en el cultivo de chocho (Lupinus mutabilis Sweet) basada en el manejo orgánico para la producción, en 5 parroquias de la provincia de Cotopaxi 2021. - Valencia Yaguana, Dania Dayanara (2022)
Pollinating insects are at risk of extinction due to farmers’ lack of knowledge about the functional role of each insect that surrounds their crops and the use of chemical products. This study was carried out in 5 parishes (Alaquez, Cusubamba, Guaytacama, Juan Montalvo, and Pujilí) of Cotopaxi province, with the specific objectives of identifying the abundance, the dominance, and the diversity of pollinating insects in the cultivation of Lupinus mutabilis Sweet. In the study sites, chromatic traps (yellow plates) with soap and water were placed during the flowering season to capture pollinating insects. In this research, the iNaturalist application identified 18 genera belonging to 4 orders as Lupinus mutabilis Sweet pollinators: Astylus, Eristalis, Carposcalis, Toxomerus, Allograpta, Cynomya, Chrysomya, Dilophus, Tachina, Tipula, Nephrotoma, Apis, Caenohalictus, Mythimna, Penaincisalia, and Hedriodiscus. Due to the abundance of insects concerning weather conditions (precipitation, altitude, and temperature), a multivariate analysis was performed; the parishes with the lowest rainfall are those with the highest abundance of insects. The temperature variable is the limiting factor for the presence of pollinating insects. The diversity and insect dominance were estimated using the Shannon-Weaver diversity index and the Simpson dominance index; it was determined that in the sectors with organically managed lupine cultivars, there is a medium diversity with values of 1.912 and a low dominance of 0.219, obtaining results that are inversely proportional to each other.